To study the survival outcomes of uncommon recurrences among patients with cervical cancer compared with loco-regional and nodal recurrences at a tertiary care center in North East India - Bridging the knowledge gap in the existing literature. - Mahendra Kumar; Upasana Baruah; Dimpy Begum; Debabrata Barmon; Jyotiman Nath; Duncan Khanikar; Karthik Chandra Bassetty (Elsevier, 2024)
Background: Recurrence rates of FIGO stage IB-IIA and IIB-IVA cervical cancer 28-64 respectively. There is a scarcity of data on the recurrence recurrence pattern for unusual sites and theirrecurrence pattern for unusual sites and its association with survival and prognosis. Objective: To study overall survival in patients with distant metastasis compared to local and regional nodal metastasis. Methods: A retrospective study was done from 1/1/2017 to 30/12/22. Cervical cancer patients post primary treatments were included. Survival was analyzed with respect to 3 groups local, regional nodalconducted from 1/1/2017 to 30/12/22. Cervical cancer patients who had received primary post-primary treatments were included. Survival was analyzed with respect to three groups: local, regional nodal, and distant metastasis. Results: 225 patients had recurrences post-completion of primary treatment, of which 105 (46.6%)(46.6 %) had local, 46 (20.4%)(20.4 %) had regional nodal, and 74 (33.3%) had distant recurrences. The median time for recurrence in local, regional nodal, and atypical recurrences were 9, 9, and 13 months (p value - <0.05), respectively. Treatment included systemic chemotherapy 122 (54.2%), metronomic therapy 19 (8.4%), palliative radiotherapy 44 (19.5%), palliative surgery 8 (3.5%) and best supportive care 30 (13.3%) patients. Median Time to treatment-death of patients after recurrence in local, nodal and distant recurrences was 17.0 months, 18.0 months and 10.0 months respectively (p value - < 0.05). Overall Survival of patients after primary treatment with local, nodal and distant recurrences was 35.0 months, 47.0 months and 50.0 months respectively (p value <0.05). Conclusion: Local recurrence is most common, followed by regional, nodal, and distant recurrences. Overall survival post recurrence was lowest for distant recurrences and highest for local recurrences however overall survival after primary treatment completion was highest for distant recurrence due to the late presen; however, tation of distant recurrences.